THE DERIVATIONAL FEATURES OF ARABIC BORROWINGS IN THE WORK OF RABGUZI - Sagdullaeva Dilfuza Karimullaevna (Western European Studies, 2023)
This article deals with the analysis of morphological peculiarities of the Arabic masdar (verbal noun), participle and adjectives used in the formation of Turkiс verbs in the work “Qisasi Rabguzi”, from the point of view of Arabic linguistics.
Keywords: Arabic borrowings; part of speech al-ism; Turkic auxiliary verb